Differential activities of bacteriophage depolymerase on bacterial polysaccharide: binding is essential but degradation is inhibitory in phage infection of K1-defective Escherichia coli. - Pelkonen, S (1992)
Host range mutants were derived from bacteriophages PK1A and PK1E specific for the K1 polysialic acid capsule of Escherichia coli. The mutants were selected for their ability to infect E. coli bacteria with a low level of the K1 capsule. A specific loss of the cleaving activity of the phage endosialidase was observed in all the mutants, while the ability to bind specifically to the polysialic acid capsule was retained. The results indicate that the polysaccharide-binding activity of the bacteriophage enzyme is essential for the infection process. The cleaving activity, in contrast, is required for the penetration of the dense polysaccharide of wild-type bacteria but is inhibitory in the infection of bacteria with a sparse capsular polysaccharide.